THE USE OF FLY ASH AND ZEOLITE MIXTURE AS BACKFILL MATERIAL IN THE RADIOACTIVE WASTE REPOSITORY - Herry Poernomo; Noor Anis Kundari; Burhani J W (Universitas Gadjah Mada, 2005)
An investigation of the contribution of fly ash in the fly ash-zeolite mixture as the backfill material on the shallow land burial of radioactive waste has been done. The experiment objective is to know the effect of zeolite particle size and fly ash-zeolite weight ratio on physical properties such as permeability (K) and dispersion characteristic such as effective dispersion coefficient (De) in the fly ash-zeolite form as backfill material. The experiment was carried out by the fixed bed method in the column filled by the fly ash-zeolite mixture with a fly ash-to-zeolite weight percent ratio of 100/0, 80/20, 60/40, 40/60, 20/80, 0/100 in the water saturated condition flown by uranyl nitrate solution at concentration (Co) of 500 ppm. The concentration of uranium in the effluents in interval 15 minutes represented as Ct was analyzed by spectrophotometer, then using Co and Ct, data effective dispersion coefficient (De) in the backfill material were determined. The experiment data showed that -400 mesh fly ash and -70+80 mesh zeolite on fly ash-to-zeolite with weight percent ratio of 40/60 with K = 5.00x10-5cm/second and De = 1.11.10-5 cm2/second can be used as backfill material.